The activist as geographer: nonviolent direct action in Cold War Germany and postcolonial Ghana, 1959–1960. (April 2019) - Hill, Christopher R.
Abstract: This article interprets nonviolent direct action campaigns against nuclear bases and tests as agents of alternative geopolitics in Cold War Germany and postcolonial Ghana. In doing so, it draws on the archives of the Direct Action Committee against Nuclear War, a British organisation, to illustrate how the activities and work of international activists entailed a repertoire of geographical skills and understanding. The activists engaged in networking to create confluences of international space, plotted logistics and maps to make practical and symbolic meanings out of the regions of the bases and tests, and through nonviolent direct action attempted to perform these as an alternative geopolitics to those of the Cold War and colonialism. Together, these processes are interpreted as part of a constructivist, spatial politics, where activists sought to shape and reshape international geographies by intervening in the relationship between space, war and peace. The more they progressed, the more the campaigns seemed to embody a separate set of socio-spatial relations by which German and Ghanaian geopolitics could be challenged and navigated. The article thus sheds light on campaign mobilisation as geography and views the spatial politics of nonviolence as a powerful paradigm in the contemporary history of international activism. Highlights: Explores geographies of nonviolent protest in Cold War Germany and postcolonial Ghana. Draws on the archival records of the Direct Action Committee, a British anti-nuclear group. Interprets nonviolent campaigns as geopolitical enterprises and projects. Shows how activists configured relations and spaces of war and peace as geopolitics. Views these spatial politics as critical to the history of environmental protest.